Agronomic Studies of Bajra (Pennisetum Typhoides) Under Dry Land Agriculture 2-Nitrogen Content of Plants as Affected By Varieties, Doses of N and Methods of Veed Control - Kumar, Vijay; Raheja, The Late P C; Chaudhary, M S (Annals of Arid Zone, 2016)
.